Analisis Proses Bisnis La Puerto Coffee & Eatery Purwokerto Menggunakan Metode SWOT dan Value Chain - Nada Salsabila Khansa; Ocha Dwi Palusi; Riani Efna Sari; Veliana Dian Maryasari; Ito Setiawan (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
The rapid growth of the culinary industry in Purwokerto has led to the emergence of numerous coffee shops with unique and competitive concepts. La Puerto Coffee & Eatery stands out as one of the leading businesses by implementing a green building concept and modern industrial design. This study aims to analyze the business processes of La Puerto using the SWOT and Value Chain methods to identify its strategic position and sustainable development opportunities. The research adopts a descriptive qualitative approach through direct observation, interviews with management and customers, and literature review. The results show that La Puerto’s main strengths lie in its eco-friendly concept, strategic location, and high-quality service, while its weaknesses include limited digitalization and underdeveloped marketing strategies. The Value Chain analysis reveals that most primary activities are effective; however, digital integration needs improvement to enhance efficiency and value creation. Overall, the combination of SWOT and Value Chain analyses provides a comprehensive understanding of business potential, suggesting that digital transformation, service innovation, and community-based marketing are key strategies for sustaining La Puerto Coffee & Eatery’s competitiveness in the dynamic culinary industry.